Preparation method and application of carbon-coated nano iron oxide composite material
By copolymerizing polyacrylonitrile with nano-ferrous oxide and forming a porous carbon-covered structure, the volume expansion problem of sodium ion battery negative electrode material during charging and discharging is solved, the circulation stability and electrochemical performance of the material are improved, and the High capacity and long life negative electrode material.
Patent Information
- Application Number
- CN202410469742.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-18
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-04-18
AI Technical Summary
The negative electrode material of sodium ion battery is prone to volume expansion during charging and discharging, resulting in reduced structural stability and poor cycle stability.
Modified polyacrylonitrile is used as a carbon precursor to combine with nanoferrous oxides, and the high carbon content of tetraphenyl aromatic ring and carboxylic group are introduced through copolymerization to form a dense three-dimensional crosslinking network to improve the carbon-forming properties and electrical electricity of the material. Chemical properties and coat nano iron tetroxide with porous carbon to alleviate the problem of volume expansion.
A sodium ion battery negative electrode material with excellent capacity and cycle stability has been achieved. The first discharge specific capacity reaches 413.5-623.4A/g, the first charge specific capacity reaches 261.3-434.5A/g, the Coulomb efficiency reaches 63.2-76.4%, and the cycle is 200 The retention rate of the loop capacity is 82.4-92.9%.
Smart Images

Figure BDA0004798564980000042 
Figure BDA0004798564980000091 
Figure BDA0004798564980000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a preparation method of a carbon-coated nano iron oxide composite material and application thereof. Background Art
[0002] Compared with lithium-ion batteries, sodium-ion batteries are more environmentally friendly, and sodium raw materials are cheap and easy to obtain, with lower costs. They are a green energy device with great development prospects. The development of high-performance negative electrode materials for sodium-ion batteries is a research trend, such as transition metal oxides, transition metal sulfides, carbon-based materials, etc. Among them, iron oxides such as ferroferric oxide and iron oxide have the advantages of high theoretical specific capacity, non-toxicity and environmental protection, and have broad application prospects. However, when iron oxides are used as negative electrode materials for batteries, volume expansion is prone to occur during the charging and discharging process, which affects the structural stability of the negative electrode material and reduces the cycle stability of the negative electrode.
[0003] Porous carbon materials have large specific surface area and good electrical conductivity. They can be used as carriers of electrode active materials and are widely used in the field of electrochemical energy. Polyacrylonitrile, as a polymer with a simple preparation method, has a little carbonization performance and can be made into nitrogen-doped carbon materials or carbon fiber materials with excellent performance. The present invention aims to use modified polyacrylonitrile as a carrier of carbon precursor and iron oxide active material to prepare high-capacity and excellent cycle stability sodium ion battery negative electrode active material. Summary of the invention
[0004] The technical problem solved by the present invention is to provide a carbon-coated nano-iron oxide composite material with high capacity and excellent cycle stability for use in negative electrode materials of sodium ion batteries.
[0005] The technical solution provided by the present invention is: a method for preparing a carbon-coated nano iron oxide composite material, comprising the following steps:
[0006] (1) Add N,N-dimethylformamide, acrylonitrile, and 4-triphenyloxybenzene maleamic acid into a reaction flask, introduce nitrogen, add azobisisobutyronitrile, heat to react, cool, filter, wash the filter cake with ethanol, and dry to obtain modified polyacrylonitrile.
[0007] (2) Add N,N-dimethylformamide and modified polyacrylonitrile to a reaction bottle, heat and stir to mix, then add ferric nitrate, stir to carry out a cross-linking reaction, dry and remove the solvent to obtain cross-linked polyacrylonitrile.
[0008] (3) placing the cross-linked polyacrylonitrile in a tube furnace and performing a pre-oxidation treatment in an air atmosphere; after cooling, mixing the product with potassium hydroxide and performing a carbonization treatment in a nitrogen atmosphere; after cooling, washing with distilled water until neutral, and drying to obtain a carbon-coated nano-iron oxide composite material.
[0009] Furthermore, the mass of 4-triphenyloxybenzene maleamic acid in (1) is 10-40% of the mass of acrylonitrile.
[0010] Furthermore, the reaction temperature in (1) is 70-80°C and the reaction time is 6-10h.
[0011] Furthermore, the mass of the ferric nitrate in (2) is 8-35% of the mass of the modified polyacrylonitrile.
[0012] Furthermore, the stirring and mixing in (2) is carried out at a temperature of 65-80° C. for 1-3 h; and the cross-linking reaction is carried out at a temperature of 40-50° C. for 6-12 h.
[0013] Furthermore, in (3), the temperature of the pre-oxidation treatment is 240-265° C., and the time is 1-2 h; and the temperature of the carbonization treatment is 750-800° C., and the time is 1-2 h.
[0014] Furthermore, the preparation method of 4-triphenyloxybenzene maleamic acid is as follows: add triphenylmethane chloride and 4-maleamic acid phenol to dichloromethane, wherein the mass of triphenylmethane chloride is 140-155% of the mass of 4-maleamic acid phenol; after dissolving, add triethylamine and 4-dimethylaminopyridine, react at 20-30°C for 12-18h, add distilled water and ethyl acetate after the reaction, extract and separate, dry the organic phase with anhydrous sodium sulfate to remove water, filter and concentrate the filtrate, wash the product with methanol, and dry to obtain 4-triphenyloxybenzene maleamic acid. The structural formula is
[0015] Furthermore, the application of carbon-coated nano-iron oxide composites in sodium ion battery negative electrode materials.
[0016] The technical effects produced by the present invention are:
[0017] The present invention copolymerizes acrylonitrile and a novel monomer of 4-triphenyloxyphenyl maleamic acid, introduces a tetraphenyl aromatic ring with a high carbon content into the polyacrylonitrile molecular chain, and the tetraphenyl aromatic ring undergoes condensed ring aromatization at high temperature to form a graphite-like aromatic hexagonal mesh structure, which is beneficial to improving the carbonization and mass residual rate of polyacrylonitrile and forming a carbon material with better electrochemical performance. At the same time, 4-triphenyloxyphenyl maleamic acid contains a carboxyl group, so a carboxyl group is introduced into the side chain of the polyacrylonitrile molecule. During the cross-linking reaction, a Fe 3+ It can form cross-linking sites with three carboxylate anions, thereby making Fe 3+ It forms a dense three-dimensional cross-linked network with modified polyacrylonitrile. Compared with the linear polyacrylonitrile molecular chain, the cross-linked polyacrylonitrile containing a dense three-dimensional cross-linked network has higher carbonization and higher mass residual rate.
[0018] The present invention uses a carbon-coated nano-iron oxide composite material as the negative electrode active material of the sodium ion battery, introduces a tetraphenyl aromatic ring with a high carbon content into the polyacrylonitrile molecular chain, and the tetraphenyl aromatic ring undergoes condensed ring aromatization at high temperature to form a graphite-like aromatic hexagonal mesh structure, which is beneficial to improving the degree of graphitization of polyacrylonitrile during high-temperature carbonization, and then forms a nitrogen-doped porous carbon material with better electrochemical performance through pore formation by potassium hydroxide, which can improve the charge and discharge specific capacity of the negative electrode material. At the same time, the carboxyl group of the polyacrylonitrile molecular side chain is very effective for Fe 3+ Complexation to convert Fe 3+ Evenly distributed in the polyacrylonitrile molecular chain, during the pre-oxidation and high-temperature carbonization process, Fe 3+ It mainly generates iron oxides such as nano-iron tetroxide and evenly disperses them in the porous carbon matrix, which improves the agglomeration problem of iron oxides such as nano-iron tetroxide, and is beneficial to improving the actual specific capacity of the negative electrode material. In addition, iron oxides such as nano-iron tetroxide can effectively alleviate the problem of volume expansion during the charge and discharge process after being coated with porous carbon, so that the negative electrode material has better cycle stability. At a current density of 0.2A / g, the first discharge specific capacity reaches 413.5-623.4A / g; the first charge specific capacity reaches 261.3-434.5A / g; and the coulomb efficiency reaches 63.2-76.4%. The capacity retention rate after 200 cycles is 82.4-92.9%. DETAILED DESCRIPTION
[0019] The following will combine the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] 70 mL of acetone, 8.64 g of maleic anhydride and 8.72 g of 4-aminophenol were added to the reaction bottle and reacted at room temperature for 2 h to generate a precipitate. The precipitate was collected by filtration and dried to obtain 4-maleamic acid phenol.
[0021] The structural formula is
[0022] Example 1
[0023] (1) Add 2.9 g of triphenylmethane and 2 g of 4-maleamic acid phenol to 8 mL of dichloromethane, dissolve them, add 1.8 g of triethylamine and 85 mg of 4-dimethylaminopyridine, react at 25° C. for 12 h, add distilled water and ethyl acetate after the reaction, extract and separate, dry the organic phase with anhydrous sodium sulfate, filter and concentrate the filtrate, wash the product with methanol, and dry to obtain 4-triphenyloxybenzene maleamic acid. The reaction formula is:
[0024]
[0025] (2) Add 50 mL of N,N-dimethylformamide, 10 g of acrylonitrile, and 1 g of 4-triphenyloxyphenylmaleamic acid into a reaction flask, introduce nitrogen, add 0.07 g of azobisisobutyronitrile, heat to 80° C. and react for 6 h, cool, filter, wash the filter cake with ethanol, and dry to obtain modified polyacrylonitrile.
[0026] (3) Add 250 mL of N,N-dimethylformamide and 20 g of modified polyacrylonitrile to a reaction bottle, heat to 65° C., and stir to mix for 2 h. Then, add 1.6 g of ferric nitrate, lower the temperature to 50° C., stir to carry out cross-linking reaction for 6 h, and dry to remove the solvent to obtain cross-linked polyacrylonitrile.
[0027] (4) 20 g (denoted as m0) of cross-linked polyacrylonitrile was placed in a tube furnace, heated to 240°C in an air atmosphere, and pre-oxidized for 2 h; after cooling, the product was mixed with 60 g of potassium hydroxide, heated to 800°C in a nitrogen atmosphere, and carbonized for 1 h. After cooling, the product was washed with distilled water until neutral, and dried to obtain a carbon-coated nano-iron oxide composite material. Then it was weighed (denoted as m) and the mass residual rate was calculated.
[0028] Example 2
[0029] (1) Prepare 4-triphenyloxybenzene maleamic acid according to the method of Example 1.
[0030] (2) Add 50 mL of N,N-dimethylformamide, 10 g of acrylonitrile, and 2 g of 4-triphenyloxyphenylmaleamic acid into a reaction flask, introduce nitrogen, add 0.08 g of azobisisobutyronitrile, heat to 80° C. and react for 6 h, cool, filter, wash the filter cake with ethanol, and dry to obtain modified polyacrylonitrile.
[0031] (3) Add 250 mL of N,N-dimethylformamide and 20 g of modified polyacrylonitrile to a reaction bottle, heat to 80° C., and stir to mix for 1 hour. Then, add 3.3 g of ferric nitrate, lower the temperature to 50° C., stir to carry out cross-linking reaction for 8 hours, and dry to remove the solvent to obtain cross-linked polyacrylonitrile.
[0032] (4) 20 g (denoted as m0) of cross-linked polyacrylonitrile was placed in a tube furnace, heated to 265°C in an air atmosphere, and pre-oxidized for 1 hour; after cooling, the product was mixed with 60 g of potassium hydroxide, heated to 750°C in a nitrogen atmosphere, and carbonized for 2 hours, cooled, washed with distilled water until neutral, and dried to obtain a carbon-coated nano-iron oxide composite material. Then weighed (denoted as m), and the mass residual rate was calculated.
[0033] Example 3
[0034] (1) Prepare 4-triphenyloxybenzene maleamic acid according to the method of Example 1.
[0035] (2) Add 70 mL of N,N-dimethylformamide, 10 g of acrylonitrile, and 3 g of 4-triphenyloxyphenylmaleamic acid into a reaction flask, introduce nitrogen, add 0.1 g of azobisisobutyronitrile, heat to 70° C. and react for 10 h, cool, filter, wash the filter cake with ethanol, and dry to obtain modified polyacrylonitrile.
[0036] (3) Add 300 mL of N,N-dimethylformamide and 20 g of modified polyacrylonitrile to a reaction bottle, heat to 65° C., and stir to mix for 3 h. Then, add 5.5 g of ferric nitrate, lower the temperature to 45° C., stir to carry out cross-linking reaction for 12 h, and dry to remove the solvent to obtain cross-linked polyacrylonitrile.
[0037] (4) 20 g (denoted as m0) of cross-linked polyacrylonitrile was placed in a tube furnace, heated to 240°C in an air atmosphere, and pre-oxidized for 2 h; after cooling, the product was mixed with 60 g of potassium hydroxide, heated to 750°C in a nitrogen atmosphere, and carbonized for 2 h. After cooling, the product was washed with distilled water until neutral, and dried to obtain a carbon-coated nano-iron oxide composite material. Then it was weighed (denoted as m) and the mass residual rate was calculated.
[0038] Example 4
[0039] (1) Prepare 4-triphenyloxybenzene maleamic acid according to the method of Example 1.
[0040] (2) Add 80 mL of N,N-dimethylformamide, 10 g of acrylonitrile, and 4 g of 4-triphenyloxyphenylmaleamic acid into a reaction flask, introduce nitrogen, add 0.11 g of azobisisobutyronitrile, heat to 75° C., react for 10 h, cool, filter, wash the filter cake with ethanol, and dry to obtain modified polyacrylonitrile.
[0041] (3) Add 300 mL of N,N-dimethylformamide and 20 g of modified polyacrylonitrile to a reaction bottle, heat to 70° C., and stir to mix for 2 h. Then, add 7 g of ferric nitrate, lower the temperature to 40° C., stir to carry out cross-linking reaction for 12 h, and dry to remove the solvent to obtain cross-linked polyacrylonitrile.
[0042] (4) 20 g (denoted as m0) of cross-linked polyacrylonitrile was placed in a tube furnace, heated to 250°C in an air atmosphere, and pre-oxidized for 2 h; after cooling, the product was mixed with 60 g of potassium hydroxide, heated to 800°C in a nitrogen atmosphere, and carbonized for 1 h. After cooling, it was washed with distilled water until neutral, and dried to obtain a carbon-coated nano-iron oxide composite material. Then it was weighed (denoted as m) and the mass residual rate was calculated.
[0043] Comparative Example 1
[0044] (1) Add 50 mL of N,N-dimethylformamide and 10 g of acrylonitrile to a reaction flask, introduce nitrogen, add 0.07 g of azobisisobutyronitrile, heat to 80°C for 6 h, cool, filter, wash the filter cake with ethanol, and dry to obtain polyacrylonitrile.
[0045] (2) Add 250 mL of N,N-dimethylformamide and 20 g of polyacrylonitrile to a reaction flask, heat to 65° C., and stir to mix for 2 h. Then add 1.6 g of ferric nitrate, lower the temperature to 50° C., stir to carry out cross-linking reaction for 6 h, and dry to remove the solvent to obtain cross-linked polyacrylonitrile.
[0046] (3) 20 g (denoted as m0) of cross-linked polyacrylonitrile was placed in a tube furnace, heated to 240°C in an air atmosphere, and pre-oxidized for 2 h; after cooling, the product was mixed with 60 g of potassium hydroxide, heated to 800°C in a nitrogen atmosphere, and carbonized for 1 h. After cooling, it was washed with distilled water until neutral, and dried to obtain a carbon-coated nano-iron oxide composite material. Then it was weighed (denoted as m) and the mass residual rate was calculated.
[0047] Comparative Example 2
[0048] (1) Add 50 mL of N,N-dimethylformamide, 10 g of acrylonitrile, and 1 g of 4-maleamic acid phenol into a reaction flask, introduce nitrogen, add 0.07 g of azobisisobutyronitrile, heat to 80° C. and react for 6 h, cool, filter, wash the filter cake with ethanol, and dry to obtain modified polyacrylonitrile.
[0049] (2) Add 250 mL of N,N-dimethylformamide and 20 g of modified polyacrylonitrile to a reaction bottle, heat to 65° C., and stir to mix for 2 h. Then, add 1.6 g of ferric nitrate, lower the temperature to 50° C., stir to carry out cross-linking reaction for 6 h, and dry to remove the solvent to obtain cross-linked polyacrylonitrile.
[0050] (3) 20 g (denoted as m0) of cross-linked polyacrylonitrile was placed in a tube furnace, heated to 240°C in an air atmosphere, and pre-oxidized for 2 h; after cooling, the product was mixed with 60 g of potassium hydroxide, heated to 800°C in a nitrogen atmosphere, and carbonized for 1 h. After cooling, it was washed with distilled water until neutral, and dried to obtain a carbon-coated nano-iron oxide composite material. Then it was weighed (denoted as m) and the mass residual rate was calculated.
[0051] Comparative Example 3
[0052] (1) Prepare 4-triphenyloxybenzene maleamic acid according to the method of Example 1.
[0053] (2) Add 50 mL of N,N-dimethylformamide, 10 g of acrylonitrile, and 1 g of 4-triphenyloxyphenylmaleamic acid into a reaction flask, introduce nitrogen, add 0.07 g of azobisisobutyronitrile, heat to 80° C. and react for 6 h, cool, filter, wash the filter cake with ethanol, and dry to obtain modified polyacrylonitrile.
[0054] (3) 20 g (denoted as m0) of modified polyacrylonitrile was placed in a tube furnace, heated to 240°C in an air atmosphere, and pre-oxidized for 2 h; after cooling, the product was mixed with 60 g of potassium hydroxide, heated to 800°C in a nitrogen atmosphere, and carbonized for 1 h. After cooling, the product was washed with distilled water until neutral, and dried to obtain a carbon composite material. Then it was weighed (denoted as m) and the mass residual rate was calculated.
[0055] Mass residual rate = m / m0×100%.
[0056] Table 1 Test of mass residual rate of composite materials
[0057] Mass residual rate (%) Example 1 50.6 Example 2 53.3 Example 3 51.2 Example 4 49.5 Comparative Example 1 41.3 Comparative Example 2 46.4 Comparative Example 3 44.7
[0058] The mass residual rate of the carbon-coated nano-iron oxide composite material of Examples 1-4 was tested to be 49.5-53.3%. This is because the copolymerization of acrylonitrile and 4-triphenyloxybenzene maleamic acid can convert the high carbon content tetraphenyl aromatic ring into When introduced into the polyacrylonitrile molecular chain, the tetraphenyl aromatic ring undergoes condensed ring aromatization at high temperature to form a graphite-like aromatic hexagonal mesh structure, which is beneficial to improve the carbonization and mass residual rate of polyacrylonitrile and form a carbon material with better electrochemical performance. At the same time, 4-triphenyloxybenzene maleamic acid contains carboxyl groups, so carboxyl groups are introduced into the side chains of polyacrylonitrile molecules. During the cross-linking reaction, a Fe 3+ It can form cross-linking sites with three carboxylate anions, thereby making Fe 3 +It forms a dense three-dimensional cross-linked network with modified polyacrylonitrile. Compared with the linear polyacrylonitrile molecular chain, the cross-linked polyacrylonitrile containing a dense three-dimensional cross-linked network has higher carbonization and higher mass residual rate.
[0059] Comparative Example 1: When preparing polyacrylonitrile, 4-triphenyloxyphenyl maleamic acid was not added, and the obtained polyacrylonitrile did not contain a tetraphenyl aromatic ring structure with a high carbon content, nor did it contain a carboxyl group, and could not react with Fe 3+ A dense three-dimensional cross-linked network is formed, which results in poor carbonization and low mass residual rate of the carbon-coated nano-iron oxide composite material.
[0060] Compared with Example 1, Comparative Example 2 uses 4-maleamic acid phenol instead of 4-triphenyloxyphenyl maleamic acid to carry out polymerization reaction with acrylonitrile. The obtained modified polyacrylonitrile contains carboxyl groups and can react with Fe 3+ The formation of a dense three-dimensional cross-linked network is beneficial to improving the carbonization and mass surplus rate (significantly higher than that of Example 1). However, the modified polyacrylonitrile does not contain tetraphenyl aromatic rings with a high carbon content, resulting in a lower carbonization and mass surplus rate than that of Example 1.
[0061] Comparative Example 3: When preparing the carbon composite material, no ferric nitrate was added and no Fe 3+ , it is impossible to form a dense three-dimensional cross-linked network, and the carbonization property and mass residual rate are lower than those in Example 1.
[0062] The carbon-coated nano-iron oxide composite material is used as the negative electrode active material of the sodium ion battery. It is added into N-methylpyrrolidone with acetylene black and polyvinylidene fluoride in a mass ratio of 8:1:1, mixed to form a slurry, and then the slurry is coated on the surface of the copper foil and dried. Finally, a punching machine is used to punch out circular pole pieces as the negative electrode of the sodium ion battery.
[0063] Using a sodium metal sheet as the counter electrode, a solution of ethylene carbonate and diethyl carbonate with a concentration of 1 mol / L NaPF6 as the electrolyte, and a glass fiber membrane as the diaphragm, a CR2032 button cell was assembled in an argon glove box. The constant current charge and discharge performance of the battery was tested in a battery test system. The voltage range was 0.1-2.0 V. The battery was tested by cyclic voltammetry using an electrochemical workstation. The voltage range was 0.1-2.0 V, and the scan rate was 0.1 mV·s -1 .
[0064] Table 2 Battery charge and discharge performance test
[0065]
[0066]
[0067] After testing the carbon-coated nano-iron oxide composite materials of Examples 1-4 as the negative electrode active material of the sodium ion battery, at a current density of 0.2A / g, the first discharge specific capacity reached 413.5-623.4A / g; the first charge specific capacity reached 261.3-434.5A / g; and the coulombic efficiency reached 63.2-76.4%. The capacity retention rate after 200 cycles was 82.4-92.9%. This is because acrylonitrile and 4-triphenyloxybenzene maleamic acid are copolymerized to introduce a tetraphenyl aromatic ring with a high carbon content into the polyacrylonitrile molecular chain. The tetraphenyl aromatic ring undergoes condensed ring aromatization at high temperature to form a graphite-like aromatic hexagonal mesh structure, which is beneficial to increase the degree of graphitization of polyacrylonitrile during high-temperature carbonization. Then, after potassium hydroxide pore formation, a nitrogen-doped porous carbon material with better electrochemical performance is formed. The charge and discharge specific capacity of the negative electrode material can be improved. At the same time, the carboxyl group of the side chain of the polyacrylonitrile molecule is effective for Fe 3+ Complexation to convert Fe 3+ Evenly distributed in the polyacrylonitrile molecular chain, during the pre-oxidation and high-temperature carbonization process, Fe 3+ It mainly generates nano-iron oxides such as ferroferric oxide and evenly disperses them in the porous carbon matrix, which improves the agglomeration problem of nano-iron oxides such as ferroferric oxide, and is beneficial to improving the actual specific capacity of the negative electrode material. In addition, nano-iron oxides such as ferroferric oxide can effectively alleviate the problem of volume expansion during the charge and discharge process after being coated by porous carbon, so that the negative electrode material has better cycle stability.
[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a carbon-coated nano-iron oxide composite material, characterized in that: The preparation method comprises the following steps: (1) Add N,N-dimethylformamide, acrylonitrile, and 4-triphenyloxyphenylmaleamic acid into a reaction bottle, introduce nitrogen, add azobisisobutyronitrile, heat to react, cool, filter, wash the filter cake with ethanol, and dry to obtain modified polyacrylonitrile; (2) Adding N,N-dimethylformamide and modified polyacrylonitrile to a reaction bottle, heating and stirring to mix, then adding ferric nitrate, stirring to carry out a cross-linking reaction, and drying to remove the solvent to obtain cross-linked polyacrylonitrile; (3) placing the cross-linked polyacrylonitrile in a tube furnace and performing a pre-oxidation treatment in an air atmosphere; after cooling, mixing the product with potassium hydroxide and performing a carbonization treatment in a nitrogen atmosphere; after cooling, washing with distilled water until neutral, and drying to obtain a carbon-coated nano-iron oxide composite material; The mass of 4-triphenyloxybenzene maleamic acid in (1) is 10-40% of the mass of acrylonitrile; The mass of the ferric nitrate in (2) is 8-35% of the mass of the modified polyacrylonitrile.
2. The method for preparing the carbon-coated nano-iron oxide composite material according to claim 1, characterized in that: The reaction temperature in (1) is 70-80°C and the reaction time is 6-10 hours.
3. The method for preparing the carbon-coated nano-iron oxide composite material according to claim 1, characterized in that: The stirring and mixing in (2) is carried out at a temperature of 65-80°C and a time of 1-3 hours; the cross-linking reaction is carried out at a temperature of 40-50°C and a time of 6-12 hours.
4. The method for preparing the carbon-coated nano-iron oxide composite material according to claim 1, characterized in that: The temperature of the pre-oxidation treatment in (3) is 240-265°C for 1-2 hours; the temperature of the carbonization treatment is 750-800°C for 1-2 hours.
5. The method for preparing the carbon-coated nano-iron oxide composite material according to claim 1, characterized in that: The preparation method of 4-triphenyloxybenzene maleamic acid is as follows: triphenylmethane and 4-maleamic acid phenol are added to dichloromethane, triethylamine and 4-dimethylaminopyridine are added after dissolution, and the mixture is reacted at 20-30° C. for 12-18 hours. After the reaction, distilled water and ethyl acetate are added, and the mixture is extracted and separated. The organic phase is dried with anhydrous sodium sulfate to remove water, and the filtrate is concentrated after filtering. The product is washed with methanol and dried to obtain 4-triphenyloxybenzene maleamic acid.
6. The method for preparing the carbon-coated nano-iron oxide composite material according to claim 5, characterized in that: The mass of the triphenylmethane is 140-155% of the mass of 4-maleamic acid phenol.
7. Use of the carbon-coated nano-iron oxide composite material obtained by the preparation method according to any one of claims 1 to 6 in a negative electrode material for a sodium ion battery.
Citation Information
Patent Citations
Cathode material of lithium ion battery and battery
CN102487141A
Preparation method and application of carbon-coated composite material
CN111276684A
Nano Fe3O4 in-situ growth N, P co-doped porous carbon negative electrode material and preparation method thereof
CN111977702A
Application of modified polyacrylonitrile, binder, negative plate and lithium ion battery
CN115064697A
Silicon-based composite negative electrode material for lithium ion secondary batteries, manufacturing method, and battery
JP2015118911A
